Antitumor activity of leaves of Himatanthus drasticus (Mart.) Plumel-Apocynaceae (janaguba) in the treatment of Sarcoma 180 tumor - Eliane Leite de Sousa; Ana Ruth Sampaio Grangeiro; Isla Vanessa Gomes Alves Bastos; Guilherme Carvalho Ribeiro Rodrigues; Maria Joselice e Silva; Falba Bernadete Ramos dos Anjos; Ivone Antonia de Souza; Cicero Ernandes Leite de Sousa (Universidade de São Paulo, 2010)
Himatanthus drasticus, also known as janaguba, is used popularly in Brazil's Northeastern region in the treatment of cancer. However, no scientific reports are available. The present study is the first investigation on the antitumor activity of crude methanolic extract from Himatanthus drasticus leaves against Sarcoma 180 tumor and on its side effects including acute oral toxicity. The OECD 423 methodology was used to study acute oral toxicity, and the STOCK methodology to assess antitumor activity. The crude extract showed low toxicity at the tested doses (50, 300 and 2000 mg/kg) administered orally. The histopathological analyses demonstrated alterations in liver lung, spleen and kidney. It also showed activity against Sarcoma 180 tumor in male Swiss albino mice, evidencing tumor growth inhibition of 67.7% and 68% at 300 mg/kg and 400 mg/kg doses, respectively. Himatanthus drasticus, conhecida popularmente como janaguba, tem uma longa história de emprego na cura do câncer no nordeste brasileiro, porém quase sem registro na literatura. O objetivo desse trabalho foi investigar a atividade antitumoral do extrato bruto metanólico das folhas de Himatanthus drasticus frente ao modelo experimental Sarcoma 180 e avaliar sua toxicidade aguda. A determinação da toxicidade aguda foi realizada segundo a metodologia da OECD 423 e o transplante do tumor sólido de sarcoma 180 foi realizado seguindo a metodologia de Stock. O extrato apresentou baixa toxicidade nas doses testadas (50, 300 e 2000 mg/kg) por via oral. A análise histopatológica apresentou alterações em nível hepático, pulmonar, baço e renal. A atividade antineoplásica apresentou inibição tumoral significativa em relação ao grupo controle nas doses de 300 mg/kg e 400 mg/kg de peso do animal com um percentual de inibição de 67.7% e 68% respectivamente. Na menor dose analisada, 200 mg/kg, o percentual de inibição tumoral foi apenas de 32.8%.